Expert Answers
hala718 eNotes educator| Certified Educator

lgx=-lg2

lg x= (-1)*lg 2

    = lg (2^-1)

     = lg (1/2)

lgx= lg(1/2)

We know that if:

lg x = lg y

Then, x=y

Since lg x = lg (1/2)

==> x= 1/2

 

neela | Student

If logx = -log2,then

logx = log2^(-1). So base being the same, x = 2^(-1). Or

x = 1/2

giorgiana1976 | Student

To find out x, first we'll have to impose constraints of existence of logarithms:

x>0

lg x=-lg 2

lg x = lg [(2)^-1]

lg x = lg 1/2

We'll use the one to one property of logarithms:

x = 1/2

Because of the fact that the solution is positive, it's convenient, so

x=1/2

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question